SOME EARLY PREDICTORS OF A RECURRENCE OF FIBRILLATION OF AURICLES IN PATIENTS WHO HAVE UNDERGONE RFA OPERATION - M. V. Mostovnek; Z. O. Shokhzodaeva; G. V. Ryabikina; E. V. Shedrina; V. E. Volkov (Евразийский Кардиологический Журнал)
The aim of this study was to identify possible ECG predictors of atrial fibrillation (AF) recurrence in the early period after radiofrequency catheter ablation (RCA). We compare P-waves parameters before and after radiofrequency catheter ablation. In total 12 lead surface ECG of forty-two patients with paroxysmal and persistent atrial fibrillation were analyzed before and after catheter ablation. The 12 lead surface ECG was recorded on sinus rhythm before and within 24-48 h after RCA . 13 patients out of 42 had atrial fibrillation recurrence. Patients with early AF recurrence were significantly older than patients with sinus rhythm. In the group of patients with AF recurrence, the duration of P wave was longer than in the group without AF recurrence. After RCA in both groups there were observed reducing of PQ interval and increasing of heart rate.